Human Milk Oligosaccharides and Associations With Immune-Mediated Disease and Infection in Childhood: A Systematic Review - Doherty, Alice M.; Lodge, Caroline J.; Dharmage, Shyamali C.; Dai, Xin; Bode, Lars; Lowe, Adrian J. (Frontiers in Pediatrics, 2018)
Complex sugars found in breastmilk, Human Milk Oligosaccharides (HMOs), may assist in early-life immune programming and prevention against infectious diseases. This paper aimed to systematically review the associations between maternal levels of HMOs and development of immune-mediated or infectious diseases in the offspring. PubMed and EMBASE databases were searched (last search on 22 February 2018) according to a predetermined search strategy. Original studies published in English examining the effect of HMOs on immune-mediated and infectious disease were eligible for inclusion. Of 847 identified records, ten articles from six original studies were included, with study quality ranging from low to high. Of three studies to examine allergic disease outcomes, one reported a protective effect against cow’s milk allergy (CMA) by 18 months of age associated with lower Lacto-N-fucopentaose (LNFP) III concentrations (OR: 6.7, 95% CI 2.0-22). Another study found higher relative abundance of fucosyloligosaccharides was associated with reduced diarrhoea incidence by 2 years, due to (i) ST-E.coli infection (p=0.04) and (ii) ‘all causes’ (p=0.042). Higher LNFP-II concentrations were associated with (i) reduced cases of gastroenteritis and respiratory tract infections at 6 weeks (p=0.004, p=0.010) and 12 weeks (p=0.038, p=0.038), and (ii) reduced HIV-transmission (OR: 0.45; 95% CI: 0.21-0.97) and mortality risk among HIV-exposed, uninfected infants (HR: 0.33; 95% Cl: 0.14-0.74) by 24-months. Due to heterogeneity of the outcomes reported, pooling of results was not possible. There was limited evidence that low concentrations of LNFP III are associated with CMA and that higher fucosyloligosaccharide levels protect infants against infectious disease. Further research is needed.